THE LEVEL OF RURAL WOMAN KNOWLEDGE IN DOMAIN ANIMALS BREEDING AND ITS RELATION WITH SOME VARIABLES FIELD STUDY IN THE TWO VILLAGES OF - Zeki H. AL-Leela (Mesopotamia Journal of Agriculture)
The present study aims basically at an assessment of the knowledge of rural area women , the animals breeding domain. Also it aims at specifying the relationship and difference between rural women knowledge and the independent related variables. Women in the two villages of AL-Shraikhan and Qubba in Nineveh governorate areas. Random sample forming a percentage of 10% using a questionnaire form (a test method) prepared specially to asses the knowledge of rural area women in this domain, the first part of it consists of measuring independent variables, the second part of it consists test to measure rural women level in animal breeding domain consisting of (26) items in regard with (cows and chicken). After making sure of its' validity, its' reliability was measured by using half split method. Then, the data were analyzed by using statistical tools: Mean, Person Coefficient, Croscal Wells, and Stepwise Regression. The results showed that 87% of rural women have middle or low level knowledge. The results also showed that the knowledge level of rural women in animals breeding domain is not related to: age, educational level of the subjects, family level of education, standard of living, and family previous work. The level of woman knowledge is related only to number of family members working in animals breeding and the sources of information depended on that particular domain.